Perceptions and attitudes of family medicine residency program directors regarding ranking applicants for residency programs using their social media accounts: A national study in Saudi Arabia - Amani M Al Qarni; Shaher Z Al Shehri; Moataza M.A. Wahab (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: In contemporary times, employers use information available on the social media (SM) to assess attitudes before interviews and recruitment of potential employees. It is used as one of the criteria to rank applicants for acceptance as residents in the Middle East. In this study, an evaluation was done of this new practice in which program directors (PDs) take into account e-professionalism for the acceptance of applicants. It was a national study of all 41 hospitals in the Kingdom of Saudi Arabia involved in Saudi board family medicine training programs. MATERIALS AND METHODS: A 36-item questionnaire was administered to PDs. Next, a focus group discussion (FGD) was held, after which there was social listening. We recorded the FGD. There was verbatim transcription and coding of the qualitative data. We held social listening using Keyhole. The percentage of positive attitudes (PPAs) was normally distributed; we tested its relationship with different factors by comparing the mean score values among categories using the Student's t-test and one-way analysis of variance. RESULTS: The average PPA toward the ranking of applicants by using their SM was 55.5% ± 17.3% (median: 56.6%). The average PPA was higher in those who used SM to communicate with residents (60.2% ±19.5%) than those who did not (49.4% ±12%; P = 0.04), even after adjusting for familiarity with Internet use. Directors in hospitals of the Ministry of Education had higher percentages; these figures, however, are not statistically significant. PDs considered the importance of establishing culturally acceptable guidelines for the assessment of e-professionalism and social reputation. CONCLUSIONS: Culturally appropriate, bioethical regulations that meet the needs of modern times should be designed. We need to solve ethical dilemmas, especially with regard to privacy in SM.